2011
DOI: 10.1017/s0066622x00004068
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Glasshouses for Human Use: Environmental Experimentation in Paxton’s Designs for the 1851 Great Exhibition Building and the Crystal Palace, Sydenham

Abstract: When the horticulturist Joseph Paxton first published his proposal to house the 1851 Great Exhibition of the Works of Industry of All Nations inside a glasshouse of enormous scale at Hyde Park, London, the scheme was praised as a more practical alternative to an earlier idea that had been put forward by the Royal Commission for the Great Exhibition’s own Building Committee. However, the feasibility of Paxton’s idea soon became the subject of concern. The use of glasshouses for the cultivation of plants was wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…It was unusual in terms of the depth and number of investigations, but the practice of empirically evaluating buildings in use was not unique to the House of Commons. In the 19th century, various public buildings had been subject of POEs, including, amongst others, the Crystal Palace (Schoenefeldt, 2011(Schoenefeldt, , 2008, the Natural History Museum (Cook & Hinchcliffe, 1996), the Royal Courts of Justice (The Times, 1887, p. 3) or Smithfield Market (Yu, 2015) and St George's Hall in Liverpool (MacKenzie, 1863). The aim of this paper, however, is not to provide a comprehensive history of early POEs, but to use the House of Commons as a site where historic practices can be studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…It was unusual in terms of the depth and number of investigations, but the practice of empirically evaluating buildings in use was not unique to the House of Commons. In the 19th century, various public buildings had been subject of POEs, including, amongst others, the Crystal Palace (Schoenefeldt, 2011(Schoenefeldt, , 2008, the Natural History Museum (Cook & Hinchcliffe, 1996), the Royal Courts of Justice (The Times, 1887, p. 3) or Smithfield Market (Yu, 2015) and St George's Hall in Liverpool (MacKenzie, 1863). The aim of this paper, however, is not to provide a comprehensive history of early POEs, but to use the House of Commons as a site where historic practices can be studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties have been observed in buildings where bioclimatic strategies were deployed, such as glasshouses, 127 including the Great Exhibition of 1851 building in Hyde Park and, subsequently, the Crystal Palace at Sydenham. 128 The operational procedures are therefore critical to gain a full understanding of the performance of these systems. After the House had been in use for fifteen years, the Speaker of the Commons and the Sergeant-at-Arms, Lord John Russell, reported that the system had been well managed.…”
Section: The Temporary House Of Commons In Use 1 8 3 6 -5mentioning
confidence: 99%
“…Recent work in this area has usefully moved beyond the technological focus of earlier studies, not least by conceptualising the subject in analytical terms as one of experiment in which hypotheses about heating and ventilation were tested in use. 9 In developing these approaches, I also draw on historians' attempts to conceive buildings in terms of discourse by proposing the design -both in evolution and as built -as an example of position-taking. Architecture emerges not as a finished object but rather as something more provisional, namely the exploration of an idea in built form.…”
Section: 'A Laboratory Of Heating and Ventilation': The Johns Hopkinsmentioning
confidence: 99%